2013
DOI: 10.1073/pnas.1217431110
|View full text |Cite
|
Sign up to set email alerts
|

TRPM8 activation attenuates inflammatory responses in mouse models of colitis

Abstract: Transient Receptor Potential Melastatin-8 (TRPM8), a recently identified member of the transient receptor potential (TRP) family of ion channels, is activated by mild cooling and by chemical compounds such as the supercooling agent, icilin. Since cooling, possibly involving TRPM8 stimulation, diminishes injury-induced peripheral inflammation, we hypothesized that TRPM8 activation may also attenuate systemic inflammation. We thus studied the involvement of TRPM8 in regulating colonic inflammation using two mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(173 citation statements)
references
References 55 publications
4
162
4
Order By: Relevance
“…1d). In accordance with our findings, Ramachandran et al observed a potent anti-inflammatory response with TRPM8 agonist icilin, but not with menthol (9). These findings indicate different mechanisms of cooling agents to modulate anti-inflammatory signalling that requires further investigation.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…1d). In accordance with our findings, Ramachandran et al observed a potent anti-inflammatory response with TRPM8 agonist icilin, but not with menthol (9). These findings indicate different mechanisms of cooling agents to modulate anti-inflammatory signalling that requires further investigation.…”
Section: Resultssupporting
confidence: 81%
“…S5e). Ramachandran et al showed that TRPM8 agonist icilin inhibited pro-inflammatory CGRP release from distal colon tissue (9). As TRPM8 is coexpressed with TRPV1 in a subset of sensory neurons and suppresses TRPV1 activity [s13], we investigated whether MPD modulates the response to TRPV1 agonist capsaicin in sensory neurons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to ;30-50% of acutely dissociated or cultured TRPM8-positive neurons that also functionally express TRPV1, suggesting species differences or artifacts related to neuronal isolation and culturing (Babes et al, 2004;Okazawa et al, 2004). Assessment of trpm8 2/2 mice and use of pharmacologic agents indicate that TRPM8 has diverse sensory roles and contributes to cold-induced allodynia and analgesia, pruritus, and inflammatory processes (Namer et al, 2008;Caspani et al, 2009;Su et al, 2011;Calvo et al, 2012;Lippoldt et al, 2013;Ramachandran et al, 2013;Shapovalov et al, 2013;Than et al, 2013). The use of selective antagonists have confirmed the involvement of TRPM8 in thermoregulation and augmented nerve excitability through voltagegated Na + channels (Gavva et al, 2012;Sarria et al, 2012).…”
Section: +mentioning
confidence: 88%
“…Among the 38 genomic loci, only two contain ion channel genes (KCNK5 23 and TRPM8 24 ). Hence, despite previous hypotheses of migraine as a potential channelopathy 5,25 , the loci identified to date do not support common variants in ion channel genes as strong susceptibility components in prevalent forms of migraine.…”
Section: Characterization Of the Associated Locimentioning
confidence: 99%